Implementation Strategies for Teaching And Learning Early Childhood In Education - Suid Saidi (Universitas Muhammadiyah Enrekang, 2021)
The goal of research Implementation of Teaching and Learning Strategies in Early Childhood Education is a Government program in an effort to improve the quality of human resources with the development of long-term investment through education activities as early as possible. Fundamentally, the Indonesian government has listed this program, as outlined in the Medium Term Strategic .Related to that, this research is aimed to see how far the effectiveness and efficiency of the process of implementing the activity specifically in the area of study. As an effort to improve the implementation of the form of activities of Early Childhood Education Implementation, the implementation process is carried out in order to obtain information as big as possible and high relevance, thus forming a focused discussion and sharpen the discussion undertaken. The problem of implementation of the strategy that runs systematically and projected is measured on the basis of the process of implementation and scope of activities in the implementation.